Effect of Jatropha Gossypiifolia Leaves in Wistar Albino Rats Against Gentamicin-Induced Biochemical Injury - Umaru, Isaac John; Akafa, Tensaba Andes; Oteng, Joseph; Akem, Ingwu Joseph; Ngbede, Ocheifa Mathew; Utioukpan, Ashaka Fidelis; Mijinyawa, Aboki Nwunuji; Akam, Odok Endurance; Ekup, Ogholo Ogholo (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2025)
Jatropha gossypiifolia L. (Euphorbiaceae), widely known as “bellyache bush,” is a medicinal plant largely used throughout Africa and America. Several human and veterinary uses in traditional medicine are described for different parts and preparations based on this plant. The protective potentials of ethanol leaf extract of Bryophyllum pinnatum against gentamicin induced biochemical injury in Wistar albino rats were evaluated using serum biochemical parameters. Twenty-five male albino rats were divided randomly into five groups A to E. Groups C and D received 100, 200 and 300 mg/kg Jatropha gossypiifolia leaves extract respectively. Groups A and B were fed with chow (normal and positive controls) while Group E received 100 mg/kg of Vitamin C. Biochemical injury was induced in rats in groups B-E with gentamicin (i.p) at the dose of 80 mg/kg body weight on the 16th day of study. The rats were then fasted for 48 h and sacrificed by cervical dislocation. Serum was collected for biochemical analysis using standard methods and analytical biochemical kits. There was a significant increase in the serum levels of AST, ALT and ALP of the rats administered with gentamicin (Group B - positive control) compared to the Group A- normal control. However, treatment of rats with 100, 200 and 300 mg/kg body weight of ethanol leaf extract of Jatropha gossypiifolia L significantly decrease these biochemical parameters compared to Group B (p < 0.05). Also, there was a significant increase in the serum levels of conjugated bilirubin and total bilirubin in Group B compared to the normal control. Rat pre-treated with 200 and 300 mg/kg body weight of extract showed significant decrease in the conjugated and total bilirubin compared to the non-treated rats in Group B (p <0.05). Serum level of urea and creatinine significantly increased in Group B compared to normal control. Rats in groups C and D pre-treated with 200 and 300 mg/kg body weight of extract showed significant decrease in the levels of urea and creatinine compared to Group B (p <0.05). There was significant decrease in the serum levels of albumin and total protein of the rats administered with gentamicin compared to the normal control. Rats pre-treated with 200 and 300 mg/kg body weight of extract showed significant increase compared rats in non-treated Group B (p <0.05). The results obtained from this study shows that the ethanolic leaf extract of Jatropha gossypiifolia L has protective functions against gentamicin-induced hepatic and nephrotic damage in Wistar albino rats.